STRUKTUR DAN DINAMIKA PERTUMBUHAN VEGETASI BERKAYU DI TAMAN WISATA ALAM GUNUNG MEJA KABUPATEN MANOKWARI - , NOVITA PANAMBE; , Dr. Ir. Ronggo Sadono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gunung Meja Natural Tourism Park Manokwari has a high diversity of woody vegetation species which are different from other species in other regions. The growth dynamic modelling for woody vegetation requires classification of endemic and non-endemic species. The objectives of this research are to identify the diversity of woody vegetation species and to propose a model of growth dynamics for woody vegetation on the monitoring plot of flora biodiversity of Gunung Meja Natural Tourism Park. The research was conducted at the plot monitoring of flora biodiversity of Gunung Meja Natural Tourism Park covering 25 ha. It employed descriptive method and document analysis. The diversity of species was observed in the seedling, sapling, poles, and tree stages and then INP and Diversity Index were calculated. The modeling used poles and tree stages, which were divided into five diameter classes, namely class I (10-<20 cm), class II (20-<30 cm), class III (30-<40 cm), class IV (40-<50 cm) and class V (50Up cm), for three years of formation, namely plot of 2005, 2006 and 2008. The established model was validated with the measurement data of 2009. The results of research on the monitoring plot of flora biodiversity indicate that the dominant species of seedlings stage was Pometia coreacea, saplings stage was Aglaia odorata, pole stage was Medusanthera laxiflora and tree stage was Pometia coreacea . The species Diversity Index all of the growth phase has high species diversity, 3.8064 for seedlings, 4.4828 for saplings, 4.3044 for poles, and 4.2270 for trees. Based on the data validation test according to the year of formation plot (plot 2005, 2006 and 2008), the plot that can be used as a model to predict the growth dynamics for woody vegetation in the future is the plot of 2008. The result of projection until the year of 2032 on the formation plot of 2008 towards the model of stand growth dynamics indicates that the number of individual/ha for endemic species decreases from 6 individuals/ha to 5 individuals/ha. Meanwhile, the number of non-endemic species increases 77 individuals/ha to 126 individuals/ha. The number of individuals/ha of all species increases from 83 individuals/ha to 131 individuals/ha.